PERAN DAN FUNGSI LEMBAGA BP4 KECAMATAN KALIANGET KABUPATEN SUMENEP DAPAT DIRASAKAN OLEH MASYARAKAT - Muhammad Kholil (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
The Role of the Kalianget BP4 Institute Sumenep functions as an official institution that supports the duties of the religious department in improving the quality of marriage and to enhance marital quality and realize a healthy household, this can be seen from the composition of the management and work programs in each field. In addition, the thing that supports BP4 is the development of exemplary sakinah and mother family movements with the establishment of West Kalianget Village as the Village of the Sakinah Family (DBKS), then reinforced by the sending of sakinah family motivators held by the East Java Regional Office. This shows that Sumenep's Kalianget BP4 has positioned its role well. In addition, BP4 serves as a forum that provides guidance and fostering towards the realization of marital conservation. The advice is given with the intention to broaden the horizons and maintain integrity and realize a family that is sure to be blessed and blessed. All of that is supported by the condition of the community that has a high level of public awareness as happened in Kalianget Sumenep.